/ti'tano/ : little constellation. - Canarezza, Rita; Castiglioni, Alessandro; Coro, Pier Paolo; Fiorini, Matteo; Morganti, Giuseppe Maria; Bombelli, Ilaria ; Leoni, Chiara ; Poli, Carlotta (Piacenza : Mousse)
Conti, Martina ; Conti, Viola ; Pozzi, Michela ; Arellano Mesina, Daniel ; Oberg, Minna ; Toumpouris, Leontios ; Christiansen, Johan Martin ; Gunnarsson, Klængur ; Atli Sigurðsson, Sigurður ; Tognozzi, Paolo ; Hilti, Anna ; Ospelt, Karin ; Kox, Vera ; Cauchi, Dustin ; Rolland, Arnaud ; Nikcevic, Teodora ; Saura, Fedora
An initiative of the Republic of San Marino dedicated to young artists from small states.
boek